Apolipoprotein C-III Levels and Incident Coronary Artery Disease Risk: The EPIC-Norfolk Prospective Population Study. Issue 6 (June 2017) - van Capelleveen, Julian C.; Bernelot Moens, Sophie J.; Yang, Xiaohong; Kastelein, John J.P.; Wareham, Nicholas J.; Zwinderman, Aeilko H.; Stroes, Erik S.G.; Witztum, Joseph L.; Hovingh, G. Kees; Khaw, Kay-Tee; Boekholdt, S. Matthijs; Tsimikas, Sotirios
Abstract : Objective—: Apolipoprotein C-III (apoC-III) is a key regulator of triglyceride metabolism. Elevated triglyceride-rich lipoproteins and apoC-III levels are causally linked to coronary artery disease (CAD) risk. The mechanism(s) through which apoC-III increases CAD risk remains largely unknown. The aim was to confirm the association between apoC-III plasma levels and CAD risk and to explore which lipoprotein subfractions contribute to this relationship between apoC-III and CAD risk. Approach and Results—: Plasma apoC-III levels were measured in baseline samples from a nested case–control study in the European Prospective Investigation of Cancer (EPIC)-Norfolk study. The study comprised 2711 apparently healthy study participants, of whom 832 subsequently developed CAD. We studied the association of baseline apoC-III levels with incident CAD risk, lipoprotein subfractions measured by nuclear magnetic resonance spectroscopy and inflammatory biomarkers. ApoC-III levels were significantly associated with CAD risk (odds ratio, 1.91; 95% confidence interval, 1.48–2.48 for highest compared with lowest quintile), retaining significance after adjustment for traditional CAD risk factors (odds ratio, 1.47; 95% confidence interval, 1.11–1.94). ApoC-III levels were positively correlated with triglyceride levels, ( r =0.39), particle numbers of very-low-density lipoprotein ( r =0.25), intermediate-density lipoprotein ( r =0.23), small dense low-density lipoprotein ( r =0.26), and high-sensitivity C-reactive protein ( r =0.15), whereas an inverse correlation was observed with large low-density lipoprotein particle number ( r =−0.11), P <0.001 for each. Mediation analysis indicated that the association between apoC-III and CAD risk could be explained by triglyceride elevation (triglyceride, very-low-density lipoprotein, and intermediate-density lipoprotein particles), small low-density lipoprotein particle size, and high-sensitivity C-reactive protein. Conclusions—: ApoC-III levels are significantly associated with incident CAD risk. Elevated levels of remnant lipoproteins, small dense low-density lipoprotein, and low-grade inflammation may explain this association. Abstract : Supplemental Digital Content is available in the text.